Activity based protein profiling to detect serine hydrolase alterations in virus infected cells - Shahiduzzaman, Md; Coombs, Kevin M. (Frontiers in Microbiology, 2012)
Activity based protein profiling (ABPP) is a newly emerging technique that uses active site-directed probes to monitor the functional status of enzymes. Serine hydrolases are one of the largest families of enzymes in mammals. More than 200 serine hydrolases have been identified but little is known about their specific roles. Serine hydrolases are involved in a variety of physiological functions, including digestion, immune response, blood coagulation and reproduction. ABPP has been used recently to investigate host-virus interactions and to understand the molecular pathogenesis of virus infections. Monitoring the altered serine hydrolases during viral infection gives insight into the catalytic activity of these enzymes that will help to identify novel targets for diagnostic and therapeutic application. This review presents the usefulness of ABPP in detecting and analyzing functional annotation of host cell serine hydrolases as a result of host-virus interaction.